A new subtype of Lynch syndrome associated with MSH2 c.354T>A (p. Y118*) identified in a Chinese family: case report and literature review - Zhong, Lan; Wang, Wenxiang; Duan, Yuanqiong; Song, Liang; Li, Zhanghuan; Yang, Kaixuan; Li, Qintong; Yin, Rutie (Frontiers in Genetics, 2024)
Background: Lynch syndrome (LS) is an autosomal dominant inherited disorder caused by mutations in mismatch repair genes. Genetic counseling is crucial for the prevention and treatment of LS, as individuals with these mutations have an increased lifetime risk of developing multiple cancers. MutS Homolog 2 (MSH2) is a Protein Coding gene that plays a key role in LS. A significant number of LS cases are linked to harmful heterozygous mutations in the MSH2 gene.Presentation: The proband was a 50-year-old endometrial dedifferentiated carcinoma patient with dMMR/MSI-H tumor negative for MSH2/MSH6 expression by immunohistochemistry. Genetic counseling and tumor gene testing were conducted using next-generation sequencing (NGS) technology, revealing a previously germline MSH2 gene nonsense mutation NM_000251.2:exon2:c.354T＞A (p.Y118*) in literature, leading to a diagnosis of LS. Further analysis of this variant in five family members of the patient confirmed its presence in all individuals, with one family member being diagnosed with colon cancer (CRC) at the age of 43. The proband received postoperative chemoradiotherapy and achieved a disease-free survival of two years, with ongoing follow-up.This study provides evidence that the MSH2 nonsense mutation c.354T＞A is a highly likely pathogenic mutation and is responsible for typical LSassociated endometrial carcinoma. It emphasizes the importance of genetic counseling for proband family members to facilitate early diagnose of LS-related carcinoma.